Membangun Koperasi Lewat Berjejaring - Muhammad Arsad Dalimunte (Universitas Proklamasi 45 Yogyakarta, 2012)
Cooperatives are economic organizations whose base is cooperation. The similarity of perceptions, beliefs, and the spirit of collectivity is the capital of cooperatives. In a cooperative organization, prosperity is the impact of cooperation. In a broader scope, to be developed cooperative must network with other cooperatives.